LncRNA NRON alleviates atrial fibrosis through suppression of M1 macrophages activated by atrial myocytes. Issue 11 (22nd November 2019) - Sun, Fei; Guo, Zhixiang; Zhang, Chengxin; Che, Hong; Gong, Wenhui; Shen, Zhiming; Shi, Yinglu; Ge, Shenglin
Abstract: The aim of the present study was to explore the role of long non-coding RNA (lncRNA) non-coding repressor of NFAT (NRON) in the atrial fibrosis and to explore whether its underlying mechanism was associated with macrophage polarization. Enzyme-linked immunosorbent assay (ELISA) analysis of pro-inflammatory cytokines revealed that NRON overexpression suppressed, whereas NRON silencing facilitated the angiotensin II (Ang II)-induced inflammatory response in primary cultured atrial myocytes. The chromatin immunoprecipitation (ChIP) results showed that nuclear factor of activated T cell 3 (NFATc3) was recruited to the promoter region of interleukin (IL) 12 (IL-12) in atrial myocytes. Further data showed that NRON overexpression suppressed, whereas NRON silencing further promoted the Ang II-induced NFATc3 nuclear transport and IL-12 expression in atrial myocytes. Moreover, RAW264.7 macrophages were incubated with the conditioned medium from the Ang II-treated atrial myocytes transfected with NRON and IL-12 overexpression vectors. IL-12 overexpression abrogated the NRON overexpression-mediated inhibition of RAW264.7 macrophage polarization to the M1-like phenotype. Additionally, mouse atrial fibroblasts were incubated with the culture medium from RAW264.7 macrophages treated as described above. IL-12 overexpression rescued the NRON overexpression-inhibited protein levels of fibrosis markers Collagen I/III in mouse atrial fibroblasts. Collectively, our data indicate that lncRNA NRON alleviates atrial fibrosis through suppression of M1 macrophages activated by atrial myocytes.